Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan Optik Voorfo di Nunukan, Kalimantan Utara - Tasya Meutia Kultsum; Murni Marlina Simarmata (Jurnal Mata Optik, 2022)
This study was aimed to analyze the effect of service quality on customer satisfaction of Voorfo Optics in Nunukan, North Kalimantan. The type of research conducted is explanatory research with quantitative approach. The number of samples in this study amounted to 30 respondents with non-probability sampling techniques with a purposive sampling approach. Data collection is done by means of the dissemination of questionnaires that have been tested validity and reliability. Respondents to this study were Voorfo Optics customers domiciled in Nunukan, North Kalimantan. The study used a simple linear regression analysis. The results showed that the quality of service had a significant positive effect on customer satisfaction. Conclusion of customer satisfaction will form a positive perception of Voorfo Optics and quality service can be done by improving the quality of service.